Analysis of filling stage for injection molding - Muhammad Arshad, Zainol Abidin (2007)
The injection or filling stage is the most important stage in injection molding process cycle. Injection or filling stage consists of the forward stroke of the screw injection unit to facilitate flow of molten material from the barrel through the nozzle and into the mold. As the first stage in the molding process in injection molding, the filling stage should give influences to the next stage. To investigate the filling stage mechanism and parameter for two plate mold, two methods have been used. The methods are machinery experimental and mold flow software analysis. The material will be used is ABS Starex SDO150 manufactured by Cheil Industries and the injection molding machine that used in machinery experimental is Arburg 520C Allrounder 800 - 2000. By doing the analysis of filling stage, the determinations of the fundamental necessary to improve the production rate without neglect the quality performance of the product that was produced. Injection pressure, injection speed and melt temperature are identified as the influences parameter in the filling stage. Finally, the analysis of filling stage in injection molding is should be considerate to achieve the good quantity rate of production without increasing the product defect.